Short Communication: Prevalence of multidrug resistant bacteria in General Surgery Hospital, Ukraine - KATERYNA KON (Smujo International, 2015)
Abstract. Kon K. 2015. Prevalence of multidrug resistant bacteria in General Surgery Hospital, Ukraine. Nusantara Bioscience 7: 102-106. Rising antibiotic resistance is a serious concern worldwide and during prescribing antibiotic treatment it is important to know general and regional tendencies in spread of multidrug-resistant strains. The aim of the present study was to evaluate regional specificity of the prevalence of multidrug-resistant strains among agents of surgical infections, to determine the most common microbial associations and to detect the most active antibiotics against multidrug-resistant bacteria. More than 60% of strains were multidrug-resistant, with the highest prevalence of resistance among Klebsiella pneumoniae, Enterobacter spp., Proteus spp., and Pseudomonas aeruginosa. Isolated multidrug-resistant bacteria showed susceptibility mainly to carbapenems and fluoroquinolones. The high prevalence of multidrug-resistant bacteria indicates the need for continuous monitoring of resistance in each hospital and to search for new methods for coping with this problem.